MgO nanoparticles: Synthesis, characterization, and applications as a catalyst for organic transformations - Dabhane, Harshal; Ghotekar, Suresh; Tambade, Pawan; Pansambal, Shreyas; Oza, Rajeshwari; Medhane, Vijay (European Journal of Chemistry, 2021)
Currently, the size and shape selective synthesis of nanoparticles (NPs) and their varied catalytic applications are gaining significant enthusiasm in the field of nanochemistry. Homogeneous catalysis is crucial due to its inherent benefits like high selectivity and mild reaction conditions. Nevertheless, it endures with serious disadvantages of catalysts and/or product separation/recycles compared to their heterogeneous counterparts restricting their catalytic applications. The utilization of catalysts in the form of nano-size is an elective methodology for the combination of merits of homogeneous and heterogeneous catalysis. Magnesium oxide (MgO) NPs are important as they find applications for catalysis, organic transformation, and synthesis of fine chemicals and organic intermediates. The applications of MgO NPs in diverse organic transformations including oxidation, reduction, epoxidation, condensation, and C-C, C-N, C-O, C-S bond formation in a variety of notable heterocyclic reactions are also discussed. The use of MgO NPs in organic transformation is advantageous as it mitigates the use of ligands; the procurable separation of catalyst for recyclability makes the protocol heterogeneous and monetary. MgO NPs gave efficacious catalytic performance towards the desired products due to high surface area. By considering these efficient merits, scientists have focused their attentions towards stupendous applications of MgO NPs in selective organic transformation. In the current review article, we summarized the synthesis of MgO NPs and numerous characterization techniques, whereas the application section illustrates their utility as a catalyst in several organic transformations. We believe this decisive appraisal will provide imperative details to further advance the application of MgO NPs in selective catalysis.